Smart tourism and poverty reduction - Shiyi TAO (Smart Cities and Regional Development Journal)
Rural poverty has constrained the social and economic development in China. Tourism is a driver for positive change, which plays a significant role in delivering sustainable solutions for people, the planet, prosperity and peace. Smart tourism is a new model of tourism informationization based on cloud computing, the mobile terminal application as the core and characterized by interactive and other efficient information services. Smart rural tourism poverty reduction is one of the most effective ways to achieve targeted poverty reduction. With the increasing integration of â€œInternet + tourismâ€, tourism has entered smart era. This study tries to analyze the application of the smart tourism, and examines the benefits to targeted poverty reduction in China. The main methodology is case study based on the operation of â€œSmart tourism supporting poverty reduction platform in Chengdu.â€ The findings as follows: smart tourism effectively solve the problems such as backward infrastructure, serious homogenization, extensive operation, lack of service concept and lack of brand concept in rural tourism development; build smart rural tourism data center and application platform to provide intelligent management system to farmers; rural tourism system as the foundation, improve the intelligent management, marketing and service of rural tourism, and promote the sustainable development. Results may be useful for government institutions, NGOs and companies as well. This study has the referential value in the targeted poverty reduction process in China, through the analyse of the latest smart tourism platform can find the current advantages and defects and make up for flaw timely. Last but no least, in order to better reduce poverty and implement smart tourism, some recommendations to the government such as continuously implementing digital transformation, government as a lead organization to coordinate all players to share tasks together, introducing explicit policies enables consistent execution of government at all levels.